Race, gender, and social class in the physical sciences: the silence of the men - Alves-Brito, Alan (Cadernos de Astronomia, 2024)
Essay extracted from the talk titled Race and Gender in the physical sciences: the problem with men’s silence, offered by the author on the second edition of As Astrocientistas: Brazilian Meeting of Girls and Women on Astrophysics, Cosmology, and Gravitation, February 07th to 10th, 2023. In this essay, I present a review of the main questions we have been working on in the physics sciences to (re)think about the place and role of men and masculinity in the discussions about race, social class, and gender in physics, taking as educational models the feminist, BIPOC, and LGBTQIA+ movements.